Adjective Lithuanianisms of the Kursenieki Language in Written Sources - Candravičius, Laurynas (Acta humanitarica academiae Saulensis, 2023)
In the 15th and 18th centuries, part of the Curonian population moved to the Curonian Spit. The settlers brought their own dialect, which became a separate ethnic minority language when they mixed with Lithuanians, Germans, and descendants of Prussians. It was mainly used in fishing and in fishermen’s homes. It did not have its own script, but various linguists and ethnographers have tried to record it using the scripts of other languages (German, Lithuanian, Latvian). Monuments of the Kursenieki language are sparse. In order to investigate the influence of the Lithuanian language on the adjectival lexis of Kursenieki adjectives from the point of view of etymology, and to examine how the impact of the Lithuanian language on Kursenieki adjectival lexis has changed over the last 150 years, the adjectival inventories of the Kursenieki language at the end of the 19th century, the beginning of the 20th century, and the end of the 20th century are compared in the article. The descriptions of adjectives done by linguists who have studied the Kursenieki language are not exhaustive, as the descriptions of the loanwords of the Kursenieki language from the Lithuanian language tend to focus on nouns and verbs. The first dictionary in the study material is Maximilian Voelkel’s dictionary Die lettischen Sprachreste auf der Kurischen Nehrung, published in Tilsit in 1879. Its adjectival inventory is the smallest of the three dictionaries taken as the study material. The second source is a glossary compiled by Juris Plāķis and included as an appendix to his study Kursenieku valoda, published in 1927. The inventory of adjectives in this glossary is the largest. The third glossary was published in 1993 in Christliebe el Mogharbel’s dissertation, Nehrungskurisch. All three dictionaries contain a combined total of 272 adjectival lexemes. The distinction between the borrowings and inheritances was based on the Latvian dictionary (Mīlenbahs ir Endzelīns, 1923–1932), the Lithuanian dictionary (Naktinienė, 2017), and the following criteria: phonomorphological, lexical, formation, semantic, and geographical. A total of 50 lexemes were identified, which can be considered Lithuanianisms. Among them, there are some problematic cases that could be assumed to be Curonisms. In total, nine Slavisms have been identified from the identified Lithuanianisms (since Kursenieki language did not have direct borrowings from Slavic languages, they are classified as Lithuanianisms). Slavisms have been divided into adapted and non-adapted Slavisms. It has been observed that the semantic group of the Christianity discourse is particularly prominent in the adjectival inventory under study. In order to better observe the interaction between Lithuanian and Kursenieki languages, additional material from a period older and later than the period under study was taken for comparison – Peter Pallas’ dictionary Linguarum totius orbis Vocabularia comparativa of the late 18th century; and the decoded material of one audio recording recorded by Dalia Kiseliūnaitė at the beginning of the 21st century, collected during expeditions in Sweden.